PERLINDUNGAN HUKUM TERHADAP HAK CIPTA SENI MOTIF TENUN SONGKET PANDAI SIKEK DITINJAU DARI UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - AKMI AZRIANTI; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Pandai Sikek woven songket is the intellectual property generated by indigenous or traditional communities. So clever sikek woven songket can be said of a copyright that must or should be protected, especially in art motif. But this still is not optimal to do because not all motifs woven clever sikek who have finished or there has been protected by the government, especially in Kanagarian Pandai Sikek Tanah Datar this is evidenced from all art motifs on Kanagarian Pandai Sikek Tanah Datar amounted to approximately 100 pieces motif but new ones have copyright certificates amounted to only 23 pieces. From this it appears that the legal protection for Tenun Songket Pandai Sikek not gone wellThe purpose of this thesis are: First, to determine the Legal Protection. Secondly, To know Barriers in Providing Legal Protection Against Copyright Weaving Art Motif Tenun Songket Pandai Sikek. Third, to know the Government's efforts to overcome barriers in Providing Legal Protection AgainstFrom the research problem there are three main things that concluded, first, legal protection against copyright art motif Tenun Songket Pandai Sikek is not running with the maximum because most motif Tenun Songket Pandai Sikek who have been there already widely known by the public crowded, so the resulting motif Tenun Pandai sikek can not be registered. Second, barriers in Providing Legal Protection Against Copyright Art Motif Tenun Songket Pandai Sikek is limited information, and the government Kanagarian could not supervise thoroughly, and in principle it is difficult to carry out protection because the motive is already widely known by the public as well as the lack of socialization of the registration rights create. Third, the Government's efforts to overcome obstacles in Providing Legal Protection Against Copyright Art Motif Tenun Songket Pandai Sikek is socializing in Kanagarian Pandai Sikek, develop the creation of craftsmen Tenun Songket Pandai Sikek, and still be preserved and developed as well as for the motive newly sought government Kanagarian to registration. The suggestion of the results of this study are. First, a need for special protection. Second, the Government should be more and more creative in doing socialization. Third, We recommend Wali Nagari more active in monitoring the results of a new creation and to develop the creation of craftsmen Tenun Songket Pandai Sikek.Keywords: Legal Protection, Copyright, Art Motif Tenun Songket Pandai Sikek.